Total Plate Numbers (ALT) Check Andyeast Mold Numbers (YM) In Kunyit Asam Jamu - Melati Yulia Kusumastuti; Safriana Safriana; Siti Aisyah Tanjung; Ainul Mardhiah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Turmeric and tamarind herbal medicineis a medicinal herb in liquid form that is made from turmeric (Curcuma domestica Val.), and tamarind fruit (Tamarindus indica L.) produced by the home industry. Jamu Gendong does not require a license to distribute, but the quality of herbal medicine must be so that it is safe for consumption. The purpose of this study was to determine the presence or absence of microbial contamination in the form of bacteria and molds/hamirs in the preparation of Jamu Gendong Kunyit Asam circulated in Harjosari I Village, Medan Amplas Subdistrict. The samples were taken from four locations: Jalan Garu II, Garu III, Garu IV, and Garu VI. The total plate count (PCA) test was carried out by dilution of stratified samples using Lactose Broth (LB) media, for bacterial tests 10 -1 to 10-5 dilutions, and for fungal tests 10-1 to 10-3 dilutions. The diluted samples were placed in medium and incubated at 45o±1o in an incubator. The bacterial total plate count was performed using Plate Count Agar (PCA) as the medium. It was incubated at 35-37oC for 24 h, and the mold/fungal test used Potato Dekstro Agar (PDA) as media and incubated at 20-25oC for 48 h. For comparison, we used packaging for herbal medicines purchased from supermarkets. Furthermore, the number of bacteria and fungi in the colon was observed and counted. The results showed fungal contamination in the home industry at Jamu Kunyit Asam. It was a sample collected from Garu II, a sample of 86×103. The samples had many colonists that exceeded the regularity set up in BPOM RI No. 32 of 2019 and SNI 19-2879-1992.